EVIDENCES OF SURFACE DIFFERENTIAL ROTATION ON THE RED DWARF PZ MON - Bondar’, N. I.; Prokof’eva, V. V. (Одеські астрономічні публікації, 2017)
Photometric behavior of the active red dwarf PZ Mori (K2e) is studied using UBVRI observations obtained with 1.25 m telescope of the SRI "Crimean Astrophysical Observatory" in 1992-2004 and V-data from the ASAS catalogue obtained in 20002006. Frequency analysis of the full V-data and colors has shown the existence of close periods – 2429d and 2500 d, respectively. Supposing that the star’s surface is covered by spots a long-term variability can be explained as changes of stellar activity during 6.5 years. After subtraction of slow periodicity some periods in the range of 15 d - 56 d with amplitudes more than 4a were found. Period P = 34d found as at the whole interval of observations as at the short selected intervals is likely close to the rotation period of the star. Steady-phase of this period indicates the existence of an active longitude where spots are generated.